Altered gut microbiota ameliorates bone pathology in the mandible of obese–insulin-resistant rats - Sathima Eaimworawuthikul (2019)
© 2019, Springer-Verlag GmbH Germany, part of Springer Nature. Purpose: The chronic consumption of a high-fat diet (HFD) induces obese–insulin resistance and impairs jawbone health via gut dysbiosis-stimulated inflammatory process. Our previous studies demonstrated that the probiotic Lactobacillus paracasei HII01, prebiotic xylooligosaccharide (XOS), and synbiotics improved several vital organ functions by reducing gut dysbiosis in HFD-induced obese rats. However, the impacts on the cellular level of jawbone microarchitecture have not been examined. Here, we hypothesized that the supplementation of L. paracasei HII01, XOS, and synbiotics ameliorated the bone microarchitectural pathology in HFD-fed rats by reducing systemic inflammation and other metabolic parameters. Methods: The dietary regimes (normal or high-fat diet) were provided to 48 male Wistar rats throughout 24-week experiment. After week 12, rats were given either a vehicle, pro-, pre-, or synbiotic for an additional 12 weeks before being killed. Then, blood analyses and bone histomorphometry of the jawbones were performed. Results: The HFD-fed rats developed obese–insulin resistance with significantly elevated systemic inflammation. Bone histomorphometry of these rats showed a decrease in trabecular thickness with increased osteoclasts and active erosion surfaces. Mineral apposition and bone-formation rates were also remarkably diminished. The treatment with pro-, pre-, and synbiotics equally improved metabolic disturbance, reduced systemic inflammation, increased trabecular thickness, decreased osteoclasts and active erosion surfaces and restored mineral apposition and bone-formation rates. Conclusion: The probiotic L. paracasei HII01, prebiotic XOS, and the synbiotics had similarly beneficial effects to improve jawbone microarchitecture in HFD-fed rats by possibly ameliorating osteoclast-related bone resorption and potentiating bone-formation activities.